2015
DOI: 10.1378/chest.15-0287
|View full text |Cite
|
Sign up to set email alerts
|

VTE Incidence and Risk Factors in Patients With Severe Sepsis and Septic Shock

Abstract: BACKGROUND: Prospective studies on the incidence of VTE during severe sepsis and septic shock remain absent, hindering effi cacy assessments regarding VTE prevention strategies in sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
208
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(229 citation statements)
references
References 25 publications
15
208
3
3
Order By: Relevance
“…The number of missed heparin doses may have also predisposed patients to VTE in this study, but this may capture a more pragmatic use of heparin prophylaxis in daily clinical practice. Compliance rates in this study were similar to compliance rates with twice/day or 3 times/day heparin in pragmatic prospective studies that found no effect of compliance on VTE development . To isolate a higher severity of illness, we included only patients who stayed at least 2 days in an ICU setting with 24 hours or more of mechanical ventilation on the basis that mechanical ventilation and immobility pose the highest risk of VTE in this population despite heparin prophylaxis .…”
Section: Discussionmentioning
confidence: 81%
“…The number of missed heparin doses may have also predisposed patients to VTE in this study, but this may capture a more pragmatic use of heparin prophylaxis in daily clinical practice. Compliance rates in this study were similar to compliance rates with twice/day or 3 times/day heparin in pragmatic prospective studies that found no effect of compliance on VTE development . To isolate a higher severity of illness, we included only patients who stayed at least 2 days in an ICU setting with 24 hours or more of mechanical ventilation on the basis that mechanical ventilation and immobility pose the highest risk of VTE in this population despite heparin prophylaxis .…”
Section: Discussionmentioning
confidence: 81%
“…(2015)410 was found as a result of a literature search for papers regarding VTE in sepsis patients. This paper discussed the results of a multicenter prospective study on the incidence of VTE based on venous echocardiography examinations of patients with sepsis or septic shock admitted to the intensive care unit (ICU), and reported that although measures to prevent VTE were taken in all cases, the incidence of VTE was high (42 of 113 cases [37.2%]).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the acute complications in sepsis (eg, organ failure, hypotension, thrombosis), septic syndromes are associated with long-term complications, including cognitive dysfunction, debilitation, and significant reductions in health-related quality of life. 3,4 As the risk and incidence of sepsis increase with age, coupled with forecasts of a sustained rise in the age of the population, sepsis will continue to be a substantial public health issue.…”
Section: Introductionmentioning
confidence: 99%